Level of Chemophobia and Relationship with Attitude towards Chemistry among Science Students - Ibrahim, Noor Hidayah Binti; Iksan, Zanaton H (FKIP-Universitas Riau, 2018)
This study was conducted to investigate the level ofchemophobia among science students and their attitude towards chemistryand their relationship. 101 Form 4 and Form 5 respondents were involved.Instrument used in this study was questionnaires comprises of three sectionsnamely demographic background, level of chemophobia (chemistry learninganxiety, chemistry evaluation anxiety and chemicals handling anxiety) andattitude towards chemistry (enjoyment of learning chemistry, enjoyment ofconducting laboratory activities, importance of chemistry in life andbehavioral tendency to learn chemistry). Research findings showed thatchemophobia among science students was at moderate level whereasstudents’ attitude towards chemistry was at high level. Research findingsalso showed that there was a moderate, negative significant relationshipbetween the three factors of chemophobia with students’ attitude towardschemistry. Based on multiple regression analysis, there was a factor inchemophobia (chemistry evaluation anxiety) that showed significantinfluence with students’ attitude towards chemistry. This study implied thatchemophobia among students should be overcome so that positive attitudetowards chemistry could be instilled and hence, this would lead to theimprovement in academic achievement and student’s participation inchemistry and science-related field.